Triangle Policy Analysis: The Social Rehabilitation Assistance (ATENSI) Policy at the Ministry of Social Affairs of the Republic of Indonesia During the Leadership Period of Saifullah Yusuf - Putri, Deby Apriliana; Imelda, Johanna Debora (International Journal of Science and Society, 2025)
The Social Rehabilitation Assistance Policy (ATENSI) is one of the strategic instruments of the Ministry of Social Affairs of the Republic of Indonesia in providing comprehensive social rehabilitation services to vulnerable groups such as children, the elderly, people with disabilities, and other marginalized groups. This study aims to analyze the dynamics of the ATENSI policy during the leadership of Saifullah Yusuf (Gus Ipul) through the Triangle Policy Analysis approach developed by Walt and Gilson, by holistically examining the elements of content, context, process, and policy actors. This study uses a qualitative approach with a descriptive design through in-depth interviews, observations, and documentation studies that are analyzed thematically. The results of the study show that the ATENSI policy has undergone substantive strengthening through regulatory improvements, integration of rehabilitation services, and digitization of data collection based on the National Integrated Socio-Economic Data (DTSEN). The social and political context, bureaucratic transformation, and the need for digital adaptation also shaped the direction of this policy. The policy process took place through the stages of problem identification, participatory formulation, collaborative cross-sector implementation, and tiered monitoring and evaluation. Policy actors, particularly the Ministry of Social Affairs, local governments, social workers, beneficiaries, and non-governmental partners, played a significant role in the successful implementation. However, challenges related to gaps in human resource capacity, implementer understanding, and infrastructure still hamper the effectiveness of the policy in the field. This study concludes that the ATENSI policy in the Saifullah Yusuf era has moved towards an inclusive, adaptive, and data-driven social rehabilitation transformation, but requires strengthening the sustainability of implementation and institutional capacity to achieve optimal social functioning outcomes.